2012
DOI: 10.1093/ntr/nts001
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of COPD Smokers and Effectiveness and Safety of Smoking Cessation Medications

Abstract: This study shows that smokers with severe or very severe COPD are predominantly males with a high degree of physical dependence upon nicotine. CAR 9-24 was 48.5%. Varenicline and bupropion yielded higher abstinence rates than NRT. Varenicline was more effective than nicotine patches: all types of treatments were safe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 12 publications
1
22
0
Order By: Relevance
“…Even severe COPD smokers (stages III and IV) can have the same abstinence rates as smokers at the earlier stages of the disease (I and II) and as the control group of smokers, if they can follow an intensive supportive program. Our results are relevant to those referred by Jimenez-Ruiz et al [31] as far as the effectiveness and safety of drug treatment for smoking cessation in smokers with severe and very severe COPD with high continuous abstinence rates (48.5%) in 24 weeks after the quit date.…”
Section: Discussionsupporting
confidence: 81%
“…Even severe COPD smokers (stages III and IV) can have the same abstinence rates as smokers at the earlier stages of the disease (I and II) and as the control group of smokers, if they can follow an intensive supportive program. Our results are relevant to those referred by Jimenez-Ruiz et al [31] as far as the effectiveness and safety of drug treatment for smoking cessation in smokers with severe and very severe COPD with high continuous abstinence rates (48.5%) in 24 weeks after the quit date.…”
Section: Discussionsupporting
confidence: 81%
“…Subsequent studies, in both clinical (e.g., Rennard et al, 2011;Nides et al, 2006;Aubin et al, 2008) and real-world settings (e.g., Boudrez, Gratziou, Messig & Metcalfe, 2011;Heydari, Talischi, Tafti & Masjedi, 2012;Jimenez et al, 2012), have confirmed the drug's efficacy at aiding cessation. Enthusiasm for the drug, however, has been somewhat dampened by concerns about its safety: specifically, since its launch, varenicline has been associated with a number of serious adverse psychological experiences.…”
Section: Introductionmentioning
confidence: 98%
“…While one study using computed tomography (CT) imaging found that FTND score was inversely correlated with CT-defined emphysema and COPD severity, the authors conceded that these findings may be largely due to selection bias and other biological processes which may lead to increased lung density in smokers [ 29 ]. Smokers with COPD have higher FTND scores, which reflects greater dependency on nicotine, compared to both smokers without COPD [ 8 ] and to individuals who quit smoking after COPD diagnosis [ 28 , 30 ]. Higher FTND scores were also associated with emergency-room admission for smoking-related conditions, compared to admission for other conditions [ 31 ], and with more negative symptoms among smokers engaged in cessation efforts [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, some highly addicted smokers with the shortest TTFC would have been excluded, biasing findings toward the null. Conversely, individuals who persist in smoking following a diagnosis of COPD are likely more addicted compared to individuals who quit post-diagnosis [ 19 , 30 ]; current smokers who report COPD at the follow-up questionnaire may be enriched with individuals with shorter TTFC, and we may therefore overestimate the association between TTFC and COPD. These two biases are in opposite directions and the overall effect is likely to be of small magnitude; our risk estimates should approximate the true association.…”
Section: Discussionmentioning
confidence: 99%